ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT SUMBER ALFARIA TRIJAYA KOTA BATAM - Lase, Beni Yusman; Yando, Agus Defri (SCIENTIA JOURNAL, 2021)
Company needs are never far from the need for information. Conditions that are increasingly sophisticated today, information systems will advance properly if supported by many factors that can make the effectiveness of the system will be achieved. One area of information systems is accounting information systems. The existence of an accounting information system cannot be ignored. The presence of PT Sumber Alfaria Trijaya which can compete with other companies and is trusted will be realized by the existence of an accounting information system that is present with its accuracy, accuracy, and speed in presenting financial information. The sample technique used to collect data in this study in sampling using probability sampling techniques using random sampling method. With the number of questionnaires as many as 342 respondents which contain factors that affect the performance of the accounting information system. The results of this study state that top management has a positive and significant effect on the performance of the accounting information system. The training program has a positive and significant effect on the performance of the accounting information system. User participation has a positive and significant effect on the performance of the accounting information system.